PEMBERDAYAAN KOMITE SEKOLAH OLEH KEPALA SEKOLAH PADA SDIT NURUL FIKRI ACEH BESAR - Idawati .; Cut Zahri Harun; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: Leadership is the principal determining school progress in implementing various school programs. In order to improve the performance of teachers, principals, guidance teachers can malakukan systematically. With the expected performance of good teachers has implications for the improvement of student achievement shown in the learning process effectively. This study uses descriptive qualitative approach. Data collection techniques used were observation, interview and documentation. Subjects were principals and teachers on Meureudu Islamic junior high school Pidie Jaya. The purpose of this study was to determine: 1) The head of the school in improving labor discipline teacher at Meureudu Islamic junior high school of Pidie Jaya, 2) principal in improving teachers' work commitment on Meureudu Pidie Jaya district, 3) principal responsibility in improving the work of teachers in Meureudu Islamic junior high school Pidie Jaya. The results showed: 1) The head of the school in improving labor discipline teacher at Meureudu to conduct training either individually or in groups via pengaraha, held a picket through daily oversight and take action for the breach of discipline. The school principal also doing by providing an appeal, reprimand, conduct classroom observations and motivate teachers to perform their duties properly. 2) The head of the school in improving teachers' work commitment on Meureudu Islamic junior high school Pidie Jaya district to include teachers in a variety of activities including, involving teachers in upgrading, involving teachers in Congress Subject Teacher (MGMP). 3) The principal responsibility of teachers in improving the Meureudu Islamic junior high school by developing performance of teachers in various teaching programs and motivate teachers to enable MGMP activities.Keywords: Principal Leadership and Teacher PerformanceAbstrak: Kepemimpinan kepala sekolah sangatlah menentukan kemajuan sekolah dalam menjalankan berbagai program sekolah. Penelitian menggunakan metode deskriptis dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan studi dokumentasi. Subjek penelitian adalah kepala sekolah dan guru pada MTsN Meureudu Kabupaten Pidie Jaya. Hasil penelitian menunjukkan: 1) Kepala sekolah dalam meningkatkan disiplin kerja guru pada MTsN Meureudu dengan melakukan pembinaan baik secara individual maupun kelompok melalui pengaraha, mengadakan pengawasan melalui piket harian dan melakukan tindakan bagi yang melanggar disiplin. Kepala sekolah juga melakukan dengan cara memberikan himbauan, teguran, melakukan observasi kelas serta memotivasi guru agar dapat melaksanakan tugasnya sebagaimana mestinya. 2) Kepala sekolah dalam meningkatkan komitmen kerja guru pada MTsN Meureudu Kabupaten Pidie Jaya dengan mengikutsertakan guru dalam berbagai kegiatan meliputi, mengikutsertakan guru dalam penataran, melibatkan guru dalam Musyawarah Guru Mata Pelajaran (MGMP). 3) Kepala sekolah dalam meningkatkan tanggung jawab guru pada MTsN Meureudu dengan melakukan pengembangan kinerja guru dalam malaksanakan berbagai program pengajaran dan memotivasi guru agar mengaktifkan kegiatan MGMP.Kata Kunci: Kepemimpinan Kepala Sekolah dan Kinerja Guru